Enantioselective total synthesis and structural reassignment of (+)-alsmaphorazine E via a traceless chirality transfer strategy. Issue 24 (2nd March 2016) - Yu, Kuan; Gao, Beiling; Liu, Zhaobo; Ding, Hanfeng
Abstract : The first enantioselective total synthesis of (+)-alsmaphorazine E was described, which led to the structural reassignment of the title molecule. Abstract : The first enantioselective total synthesis of (+)-alsmaphorazine E has been achieved through a traceless chirality transfer strategy, which also enabled structural reassignment of the natural product. Key features of this efficient approach entail a catalytic intramolecular oxidative cyclization, a diastereoselective oxidative cyclic aminal formation and a radical cyclization/transannular aza-Michael addition cascade.